Is global human well-being peaking? - Grafton, R. Q.; Chu, L.; Kompas, T.; Fanaian, Safa (Elsevier, 2025)
We undertook multiple individual country time trend analyses using post 1990 data and estimated that real GDP per capita and life expectancy at birth, together, are projected to have peaked before 2050 for about two-thirds of the world’s population and at levels far below their current values in upper high-income countries. We found there are ‘flourishing’ countries where human well-being is already high and will likely increase, but a much larger group of ‘languishing’ countries where human well-being has peaked, or will likely peak, before 2050. We estimated a positive time-series association between real per capita income and broader composite (e.g. Human Development Index) well-being indicators, but this association diminishes in the level of real per capita income. A mitigation response to peaking average global human well-being is cross-country monetary transfers from higher- to lower-income countries. Thus, we calculated two possible global transfers: one equal to 1.3 trillion/year USD in total and an alternative based on the projected climate change damage to low to middle-income countries. Each global transfer would impose only a relatively small proportional cost on the national income of contributing countries but could provide very large average human well-being benefits to the poor and most vulnerable in low-income countries.